Kulliyyah of Information and Communication Technology (KICT) postgraduate system - Mantoro, Teddy; Ayu, Media Anugerah; Yusop, Ahmad Haitham (IIUM Press, 2011)
Kulliyyah of Information and Communication Technology (KICT) Postgraduate System is a system built to facilitate the supervisor's supervision task in managing their records to be more effective and efficient through a web based system and replace the current manual process. The system will allow supervisors, Head of Department and Deputy Dean Postgraduate and Research to track research progress, student study status,produce summary report and also store related data during the research process. As for student, they can submit progress report and end of semester report online using this system. It is hoped that the existence of this system will help to ease all of the aforementioned processes in a more efficient way